Using Darwin's pangenesis correspondences to examine science as a human endeavor - Lorsbach, Anthony; Meyer, Allison
This lesson used the correspondence of Charles Darwin as an exploration of nature of science (NOS) in a historical context. Specifically, we used his original correspondence about his (3z(Bprovisional hypothesis(3y (Bof pangenesis as a novel way to explore a scientist$1 (Bs social community. Darwin$1 (Bs community of friends and colleagues in the natural sciences at the time of his writing of his 1868 book Variations formed the basis of this lesson. One basic descriptor of NOS, science as a human endeavor, was used to drive explicit reflection. These letters were rich in detail regarding the idea of science as a community of practice. Our elementary education students$1 (Bresponses indicate the letters surprised them in how personal the correspondents were with one another and how reliant Darwin was on his friends and colleagues for input on his work. Darwin became human as students imagined Darwin$1 (Bs mental state and how he wrestled with his idea and made it public. Students learned that despite Darwin$1 (Bs fame, his idea of pangenesis lacked empirical evidence and thus received little support. They discovered an eminent scientist who was insecure and nervous and who worked hard to develop, study, and publicize his novel idea. This contrasts with popular views of major scientific figures as natural geniuses rather than their success resulting from labor and perseverance.s
Keywords: Nature of science; History of science; Science teaching; Teacher training